2020
DOI: 10.20956/jmsk.v17i2.11984
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Divorce Dynamics Models

Abstract: This article examines the mathematical model of divorce. This model consists of four population classes, namely the Married class (M), the population class who experiences separation of separated beds (S), the population class who is divorced by Divorce (D), and the population class who experiences depression or stress due to divorce Hardship (H). This study focuses on the stability analysis of divorce-free and endemic equilibrium points. Local stability was analyzed using linearization and eigenvalues ​​metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…All the above situations were explained numerically as well as graphically. Toaha 32 proved that at most two outcomes R1 and R2 are possible when the model does not involve the intraspecific competition among predators, and both the functional and numerical responses are of Holling type I. We arrived at the same conclusion with Toaha 32 when the intraspecific competition is present among predators (analytical proof is given in Appendix ).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…All the above situations were explained numerically as well as graphically. Toaha 32 proved that at most two outcomes R1 and R2 are possible when the model does not involve the intraspecific competition among predators, and both the functional and numerical responses are of Holling type I. We arrived at the same conclusion with Toaha 32 when the intraspecific competition is present among predators (analytical proof is given in Appendix ).…”
Section: Discussionsupporting
confidence: 62%
“…Toaha 32 proved that at most two outcomes R1 and R2 are possible when the model does not involve the intraspecific competition among predators, and both the functional and numerical responses are of Holling type I. We arrived at the same conclusion with Toaha 32 when the intraspecific competition is present among predators (analytical proof is given in Appendix ). Therefore, we conclude that the variety of such delay‐induced dynamical behaviors in a single and relatively simple model are due to the presence of the distinct numerical response function.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…They concluded that harmonization and limitation of social contagion will reduce the rate of divorce. A model of three compartments; married, divorced, and separated was formulated by [9] which was extended by [20]. In their study, they concluded that increasing the number of marriages that go into separation and educating them along with reducing contact with infectious divorcees help in combating the divorce epidemic.…”
Section: Introductionmentioning
confidence: 99%